Effect of pH on Phytochemical and Antioxidant Potential of Satawar Tubers (Asparagus Racemosus Willd.) - Devi, Parvesh; Singh, Sushila; Sangwan, Seema; Sihag, Sheetal; Moond, Monika (Journal of Antioxidant Activity, 2021)
Plants are an important source of medicines since ancient times. The traditional system medicine’s use a variety of native plants to diagnose, prevent, and eliminate acute and chronic diseases.Asparagus racemosus(Willd.), also have been widely used for medicinal purpose and its extensively distributed in the tropics and subtropics of India, commonly known as Satawar, belongs to the family Asparagus. The purpose of this was to identify the phytochemicals and to assess the antioxidant potential in aqueous extracts prepared at different pH levels of Satawar tubers. The maximum amount of phenolics and flavonoids content was present at pH 9 i.e.18.88mg GAE/g and 2.83mg CE/g. The total antioxidant capacity was highest at pH 2 (15.96mg AAE/g) and IC50 values of DPPH free radical scavenging activity was the lowest at pH 7, 2582.85µg/mL. According to the whole study, this plant is a very good source of phytochemicals and acts as a powerful antioxidant.
Keywords: Antioxidant potential; flavonoids; phenolics; secondary metabolites; total antioxidant capacity.